The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3892/mmr.2016.5158
|View full text |Cite
|
Sign up to set email alerts
|

TLR2/NFκB signalling regulates endogenous IL-6 release from marrow-derived mesenchymal stromal cells to suppress the apoptosis of PC12 cells injured by oxygen and glucose deprivation

Abstract: Two previous studies published by our group identified that mesenchymal stromal cells (MSCs) conferred neuroprotection in a rat model of hypoxic-ischaemic brain damage (HIBD), and that MSCs secreted abundant interleukin-6 (IL‑6) when co‑cultured with oxygen and glucose deprivation (OGD)‑injured PC12 cells. The present study has further investigated the role of IL‑6, and explored potential signalling pathways in vitro. In vitro models were established by co‑culturing OGD‑injured PC12 cells with MSCs. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The observed secretory profile of cPMSCs in combination with existing MSC literature suggests the potential for use as a therapeutic; cPMSCs secreted IL‐6, IL‐8, MCP‐1, and VEGF, all paracrine factors secreted by human PMSC lines in our previous studies . IL‐6 is an immunomodulatory cytokine with demonstrated in vitro and in vivo neuroprotective capabilities . IL‐8 is another cytokine with immunomodulatory properties that also promotes angiogenesis .…”
Section: Discussionmentioning
confidence: 62%
“…The observed secretory profile of cPMSCs in combination with existing MSC literature suggests the potential for use as a therapeutic; cPMSCs secreted IL‐6, IL‐8, MCP‐1, and VEGF, all paracrine factors secreted by human PMSC lines in our previous studies . IL‐6 is an immunomodulatory cytokine with demonstrated in vitro and in vivo neuroprotective capabilities . IL‐8 is another cytokine with immunomodulatory properties that also promotes angiogenesis .…”
Section: Discussionmentioning
confidence: 62%
“…A recent positron emission tomography (PET) imaging study showed that MSCs remained viable for 3 weeks when injected into canine IVDs in an annular lesion model of disc degeneration yet beneficial effects with regards to matrix repair and alleviation of LBP were measurable for up to 6 months post operatively (PO). Further modes of action for MSCs in the healing process have therefore been proposed based on the ability of MSCs to enhance resident cell viability and/or proliferation, reduce cell apoptosis, and, in some cases, modulate immune responses . These are due to paracrine effects due to secreted growth factors, cytokines, and hormones from the MSCs and cell‐cell interactions mediated through communicating nanotubes, which convey extracellular vesicles containing reparative peptides/proteins, mRNA, and microRNAs .…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported for human placenta derived MSCs [ 95 ], Long et al [ 53 ] and Amorim et al [ 54 ], using a cytokine array demonstrated that unstimulated and stimulated DPCs secrete a number of paracrine factors. VEGF and MCP-1 are implicated in both neuroprotection and angiogenesis [ 56 , 57 ], IL-6 is an immunomodulatory cytokine with in vitro and in vivo demonstrated neuroprotective capabilities [ 58 ], and IL-8 is an immunomodulatory cytokine that promotes angiogenesis [ 59 ].…”
Section: Canine Mesenchymal Stem Cells From Foetal Adnexamentioning
confidence: 99%